PADMASANA BALI DALAM PERSPEKTIF KAJIAN BUDAYA - Anak Agung Gde Putera Semadi (Widyasrama, 2021)
Palinggih Padmasana is a sanctified building to worship Ida Sang Hyang Widhi Wasa/God Almighty in His various manifestations. It does not only has a varying forms, but also different designation, function, and meaning of symbols which differ based on its location. Historycally, the existence of this palinggih was only known around 15th century especially duringthe reign of Dalem Waturenggongwhich was indicated by the arrival of a powerful Shiwa priest to Bali named Danghyang Dwijendra with a sacred mission of perfecting the order of Hindu life forms Tri Murti to Tri Purusa concept. Each function and symbol in palinggih Padmasana truly reflects the nobility of invaluable meaning, therefore, Padmasana is a symbol of the universe for Hindus. Through theperspective of cultural studies which is accompanied by the implementation of descriptive analysis method, this research topic was successfully studied critically, logically, and systematically.